2008
DOI: 10.1111/j.1538-7836.2008.03102.x
|View full text |Cite
|
Sign up to set email alerts
|

Family history of myocardial infarction is an independent risk factor for venous thromboembolism: the Tromsø study

Abstract: To cite this article: Braekkan SK, Mathiesen EB, Njølstad I, Wilsgaard T, Størmer J, Hansen JB. Family history of myocardial infarction is an independent risk factor for venous thromboembolism: the Tromsø study. J Thromb Haemost 2008; 6: 1851-7.Summary. Background: Recent studies indicate that arterial cardiovascular diseases and venous thromboembolism (VTE) share common risk factors. A family history of myocardial infarction (MI) is a strong and independent risk factor for future MI. Objectives: The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
5
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 34 publications
(55 reference statements)
12
113
5
8
Order By: Relevance
“…Altogether, these studies support the hypothesis that platelet activation may also play a role in the pathogenesis of VTE. Recent studies indicate a link between arterial cardiovascular diseases and VTE, suggesting that arterial thromboembolism and VTE may share common genetic or environmental risk factors [7,[31][32][33]. Age, BMI and acute infections are well-established risk factors for both arterial and venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these studies support the hypothesis that platelet activation may also play a role in the pathogenesis of VTE. Recent studies indicate a link between arterial cardiovascular diseases and VTE, suggesting that arterial thromboembolism and VTE may share common genetic or environmental risk factors [7,[31][32][33]. Age, BMI and acute infections are well-established risk factors for both arterial and venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Age, BMI and acute infections are well-established risk factors for both arterial and venous thrombosis. However, large prospective cohort studies have failed to show an association between VTE and other traditional cardiovascular risk factors, such as smoking, blood pressure, triglycerides, and cholesterol [3,32,34]. Increased levels of MPV are found in patients with coronary artery disease [14,15], and MPV has been identified as an independent risk factor for myocardial infarction and stroke [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, acute reactions to infectious agents are associated with an increased risk of both arterial ischaemic events and VTE and are accompanied by both arterial and venous endothelial dysfunction (40,43,44); increased circulating levels of some biomarkers of endothelial dysfunction, like endothelial microparticles or P-selectin, are associated with both an enhanced risk of cardiovascular events and of VTE (45)(46)(47); recent data have shown in patients with VTE an increase of circulating fibronectin, an endothelium-released plasma factor previously shown to correlate with arterial endothelial dysfunction (48,49); several other clinical conditions characterised by an impaired arterial endothelial function, like airpollution, chronic HIV infection, a family history of myocardial infarction, the metabolic syndrome, rheumatoid arthritis and microalbuminuria, have been reported to be associated not only with an increased risk of arterial events but also of venous thrombosis (12,14,16,19,21,22,(50)(51)(52).…”
Section: (ǡTable 2)mentioning
confidence: 99%
“…Furthermore, the increased incidence of VTE in patients with risk factors for arterial cardiovascular events points too to a common pathogenesis (6). Indeed, a number of studies, with different design and in various clinical settings, have shown an increased risk of VTE associated with most of the classic or novel risk factor for ischaemic cardiovascular disease (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) (ǠTable 1).…”
Section: The Association Between Venous and Arterial Thrombosismentioning
confidence: 99%
“…8 Casecontrol investigations have indicated an association between venous thrombosis and dyslipidemia, and smoking, 10,11 but cohort studies have not confirmed these findings. [12][13][14][15] It is still uncertain whether hypertension and diabetes are significant risk factors for venous thrombosis. 9,12,16,17 There is only one published study investigating the role of a positive family history for arterial thrombosis.…”
Section: Introductionmentioning
confidence: 99%